El antonionismo del antiguo Reino Bakongo. Su repercusión en Cuba / The antonionism of the ancient kingdom of Bakongo. Its repercussion in Cuba (Islas, 2021)
La cristianización del antiguo Reino de los Bakongos constituyóun proceso de interés para entender las variantes religiosas en África y porqué también se trasladaron a América. El catolicismo se extendió en Áfricaconjuntamente con la colonización político-cultural. Pero las raíces de las religionesautóctonas se unieron a guerras por el poder dando lugar a variantesreligiosas, entre ellas el antonionismo, corriente mesiánica de veneracióna San Antonio con características del animismo africano que se traspasa aAmérica, y no es casual que muchos cabildos congos de Cuba veneren aSan Antonio, siendo estos rituales herederos del antonionismo africano.The Christianization of the ancient Kingdom of Bakongo wasa process of interest to understand the religious variants in Africa, andwhy they also moved to America. Catholicism spread in Africa togetherwith the political-cultural colonization. Nonetheless, the roots of nativereligions joined to wars for power, which gave rise to religious variantssuch as antonionism, a messianic current of veneration for Saint Anthony(San Antonio in Spanish) with characteristics of African animism that istransferred to America; and it is not coincidence that many Congolesecabildos in Cuba venerate Saint Anthony, since these rituals were inheritedfrom African antonionism.
Keywords: antonionismo; congos; Reino de los Bakongos; antonionismo africano; Kingdom of Bakongo